A mandible from the Middle Pleistocene Hexian site and its significance in relation to the variability of Asian Homo erectus. Issue 4 (21st January 2017) - Liu, Wu; Martinón‐Torres, María; Kaifu, Yousuke; Wu, Xiujie; Kono, Reiko T.; Chang, Chun‐Hsiang; Wei, Pianpian; Xing, Song; Huang, Wanbo; Bermúdez de Castro, José María
Abstract: Objectives: This study presents the first detailed morphological description and comparison of a Middle Pleistocene hominin mandibular fragment (PA 831) and associated teeth from the Hexian site in Eastern China. We aim to investigate where the Hexian mandible fits within the genus Homo variability in the light of an increased and better characterized Asian fossils record. Methods: Comparative samples include Pleistocene Homo mandibles and teeth from Africa, Asia, and Europe, as well as earlier African hominins ( Australopithecus and early Homo ) and Holocene recent humans. Both conventional morphological description and metric analysis were used. In addition, virtual reconstructions of the enamel dentine junction (EDJ) surface, pulp cavity, and roots with micro‐CT were used to the mandible and teeth. Results: The Hexian mandible is characterized by a plesiomorphic structural pattern for the Homo clade, with strong corpus robustness and a subparallel and low‐positioned mylohyoid line that differentiates the swollen subalveolar planum from the shallow subalveolar fossa. Features that are derived compared to early Homo include a moderately curved dental arcade, a well‐developed lateral prominence placed at the M2 ‐M3 level, and multiple mental foramina. The Hexian mandible's complex enamel surface and strong, stout root structure are primitive traits for the Homo clade. Finally, the highly crenulated "dendrite‐like" EDJ found in the molars may represent a dental feature specific to the continental Asian Homo erectus, but more data is needed to confirm this. Conclusions: Mandibular and dental features indicate that the Hexian mandible and teeth differ from northern Chinese H. erectus and European Middle Pleistocene hominins, but show some affinities with the Early Pleistocene specimens from Africa ( Homo ergaster ) and Java ( H. erectus ), as well as the Middle‐Late Pleistocene mandible from Penghu, Taiwan. Compared to contemporaneous continental Asian hominin populations, the Hexian fossils may represent the survival of a primitive hominin, with more primitive morphologies than other contemporaneous or some chronologically older Asian hominin specimens.